Menakıb-ı Hasan Cihangiri ve cihangirilik yolu - Süsleyici , Fatih (My University, 2004)
Hasan Burhâneddin Cihangîrî'nin hayatı, târikatı ve halifelerini anlatan Tuhfetü's-Sâlikîn ve Hediyyetü'l-Mütereşşidîn ve Tezkiratü'l-Müteahhirîn adlı menâkıbnâmelerin analizini yapmadan önce giriş bölümünde; Osmanlı Devleti'nin o dönemki siyasî, içtimaî, ilmi, kültürel, sanatsal ve özellikle tasavvuf hakkında bilgiler vermeye çalıştık. Daha sonraki bölümde; Hasan Burhâneddin Cihangîrî'nin hayatını matbû eserler ve özellikle menâkıbnâmeden yararlanarak doğumunu, çocukluğunu, tahsil hayatını, tasavvufa intisabını, İstanbul'a hicretini, kerametlerinden bazılarını, irşad faaliyetlerini, vefatını, camii ve tekkesi hakkında bilgiler vermeye çalıştık. İkinci bölümde de Cihangiriyye tarîkatı ve özelliklerini anlatmaya çalıştık. En son bölümde ise tezimizin asıl konusu olan menâkıbnâmeyi, nüshalarını tavsif ederek tahkik ettik. Before analysing biographies called Tuhfetü's- Salikin, Hediyyetü'l Mütereşşidin and Tezkiratü'l Müteahhirin which consist of the life of Hasan Burhaneddin Cihangiri, his dervish order and his caliphs; we worked on to expose overall statement about political, sociological, scientifical, cultural, aesthetical and especially mystical (tasavvufi) aspects of the relevant time interval in Ottoman Empire at the introductory part of the thesis. In the first part, through using printed books and especially biographies,we give more information about the life of Hasan Burhaneddin Cihangiri such as his childhood years, years in education, how he becomes gifted in mystics, his journey to Istanbul,his some of the mystic miracles,his irşad- indicating the right path- activities, his death, his mosque and his tekke. In the second part,we explain the Cihangiriyye Tarikat- dervish order- and some of its characteristics. Finally in the last part, we try to analyze and compare copies of the biographies which are the main subject of our thesis.
Keywords: Din; İslam ahlâk ve adâbı; İslam Dini; Tasavvuf